Pengujian Aplikasi Pemesanan Tiket Bus dengan QR Code Menggunakan Black Box - Reza Alif Anugrah; Fathul Ghina; Dwi Nur Febrianto; Munandar; Aries Saifudin (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
At this time there are still many who have difficulty buying tickets, especially when buying bus tickets, where customers do not have time to buy directly at the bus ticket purchase counter due to the distance to the ticket purchase location and the cost of purchasing bus tickets which is quite expensive, so to make things efficient time there will be a test of the bus ticket purchase application system.The bus ticket reservation and purchase system is an application system required by users of bus ticket reservation transactions. Because it is about payment transactions via online transactions. If there is an error, it may affect your booking of bus tickets. Testing the bus ticket booking application ensures that the system is developed to test the application. This application is tested using selentesting and matches the application test whether everything is running or not. This application has a login and registration form that I test with selenium methods. Testing this application tests the system the program is running on. Also, the results of testing this bus ticket application adjusted the standard conditions of the tests, and the results ran without syntax errors.